Engineered to Sell European Émigrés and the Making of Consumer Capitalism - Logemann, Jan (University of Chicago Press, 2019)
Forever immortalized in the television series Mad Men, the mid-twentieth century marketing world influenced nearly every aspect of American culture-music, literature, politics, economics, consumerism, race relations, gender, and more. In Engineered to Sell, Jan Logemann traces the transnational careers of consumer engineers in advertising, market research and commercial design who transformed capitalism, from the 1930s through the 1960s. He argues that the history of marketing consumer goods is not a story of American exceptionalism. Instead, the careers of immigrants point to the limits of the "Americanization" paradigm. First, Logemann explains the rise of a dynamic world of goods by emphasizing changes in marketing approaches increasingly tailored to consumers. Second, he looks at how and why consumer engineering was shaped by transatlantic exchanges. From Austrian psychologists and little-known social scientists to the illustrious Bauhaus artists, the émigrés at the center of this story illustrate the vibrant cultural and commercial connections between metropolitan centers: Vienna and New York; Paris and Chicago; Berlin and San Francisco. These mid-century consumer engineers crossed national and disciplinary boundaries not only within arts and academia but also between governments, corporate actors, and social reform movements. By focusing on the transnational lives of émigré consumer researchers, marketers, and designers, Engineered to Sell details the processes of cultural translation and adaptation that mark both the mid-century transformation of American marketing and the subsequent European shift to "American" consumer capitalism